Pengaruh Senam Prolanis terhadap Penurunan Tekanan Darah pada Penderita Hipertensi di Puskesmas Raya - Nasution, Dian Permata; Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Ginting, Isaharpika Br; Gea, Yosni Handayani (Jurnal Riset Hesti Medan, 2025)
The World Health Organization American Heart Association in 2015 stated that currently hypertension sufferers in the world have reached around 970 million sufferers, around 330 million are in developed countries and 640 in developing countries. The purpose of this study is to determine the effect of PROLANIS exercise on reducing blood pressure in hypertension sufferers at the Singosari Pematangsiantar Health Center. This study uses a quantitative method. The design of this study uses the Quasi Experiment method with the research design "One group pretest posttest design". The sample in this study was the elderly as many as 47 respondents. Data analysis was carried out using univariate analysis and bivariate analysis using Wilcoxon. Results: The results of the study were analyzed using a t-dependent test showing that there was an effect of PROLANIS exercise on reducing blood pressure in hypertension sufferers with a P-value of 3,000. This study is expected to maximize the implementation of the PROLANIS program so that the objectives of this activity can be achieved optimally. Conclusion: Implementation of elderly gymnastics can reduce blood pressure in hypertension patients. It can be used as a benchmark for compiling nursing interventions on the influence of PROLANIS gymnastics on reducing blood pressure in hypertension patients at Permatangsiantar Health Center in improving the quality of health services.